15 Minute SPANISH Learn in Just 12 Weeks - Bremon(3, (BAnas (New York DK, 2012)
whether starting from scratch or just in need of refresher. there is no easier way to learn Spanish fast
including 3 books :n1. 15 minute Spanish- n2. Spanish visual phrase book- n3. Spanish easy grammar
13
Keywords: spanish -- learn -- audio vishual; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs